Fertility awareness, intentions concerning childbearing, and attitudes toward parenthood among female health professions students in Saudi Arabia - Alfaraj, Samaher; Aleraij, Sheikah; Morad, Sara; Alomar, Norah; Al Rajih, Haneen; Alhussain, Halah; Abushrai, Farah; AlThubaiti, Alaa (International Journal of Health Sciences, 2019)
Background: Postponing childbearing is becoming increasingly common among higher education students. The awareness about the extent of the age-related decline in female fertility is unknown in Saudi Arabia. Objective: The main aim of the study was to assess fertility awareness, particularly age-related fertility decline, and attitudes toward parenthood. Methods: A cross-sectional study was conducted utilizing a self-administered questionnaire which was filled by 248 female students in multiple colleges at King Saud Bin Abdulaziz University for Health Science (KSAU-HS). The questionnaire adapted from the Swedish Fertility Awareness Questionnaire; it contains 31 items that can be grouped into five categories: Sociodemographic characteristics, the future intention of having children, important circumstances for the decision to have children, which have seven items, participant perception regarding motherhood impact on life, and knowledge about fertility issues. Results: Nearly 80% of undergraduate female students want to have children. They have a positive attitude toward parenthood. On the other hand, 85% of the respondents plan to postpone having children until they finish their studies and have a stable career. Conclusion: The study revealed that most of the students are concerned about childbearing. However, the participants are not aware of the decline in fertility caused by aging. More effort should be directed toward spreading awareness regarding age-related fertility decline among health profession students and the general population.